Therapeutic targeting of STAT pathways in CNS autoimmune diseases - Egwuagu, Charles E. (Landes Bioscience, 2013)
Signal transducers and activators of transcription (STATs) transduce extracellular signals that regulate the initiation, duration and intensity of immune responses. However, unbridled activation of STATs by pro-inflammatory cytokines or growth factors contributes to pathogenic autoimmunity. In this review, we briefly discuss STAT pathways that promote the development and expansion of T cells that mediate two CNS inflammatory diseases, multiple sclerosis (MS) and uveitis. Particular focus is on animal models of MS and uveitis and new approaches to the treatment of CNS autoimmune diseases based on therapeutic targeting of Th17 cells and STAT pathways.